V-Grooved Gold-Coated Photonic Crystal Fiber Sensor for Sensitivity Analysis of Tumor Detection in the Near-Infrared Region - Sharma, Dr. Sunil; Shieh, Prof. Chin Shiuh; Horng, Prof. Mong-Fong; Sen, Dr. Riya; Chakrabarti, Prof. Prasun; Das, Dr. Sandip (Photonics Letters of Poland, 2025)
The proposed study introduced a V-Grooved Gold-Coated Photonic Crystal Fiber (PCF) sensor, which exhibits top-notch performance in tumor identification when operating in the near-infrared (NIR) spectral range from 700–2500 nm. When using a V-groove structure attached to a 0.05 μm gold (Au) coating, it enhances the surface plasmon resonance (SPR) effect, which improves both light-matter interaction and sensor operational efficiency. Performance analysis in COMSOL Multiphysics demonstrated that the sensor possesses a high sensitivity of 10,714.28 nm/RIU and a resolution of 1.92 × 10⁻⁵ RIU enabling it to detect slight variations in biological tissue refractive index effectively. Response wavelength shifts were confirmed through effective mode index analysis, where strong mode confinement occurred when testing normal cells (RI = 1.35) compared to tumor-infected cells (RI = 1.40–142). The proposed PCF had its confinement loss optimized to remain below 10⁻³ dB/cm, producing minimal propagation loss while keeping optical efficiency high. Full Text: PDF References R.K. Verma, S. Kumar, A. Jindal, "Highly Sensitive V-Grooved SPR PCF Biosensor for Cancer Detection", Optical and Quantum Electronics 55(5) (2022). CrossRef S. Sharma, L. Tharani, "Photonic Crystal Fiber Sensor Design for Enhanced Tumor Detection: Structural Optimization and Sensitivity Analysis", Photonics Lett. Poland 16(2), 25 (2024). CrossRef S. Yadav et al. "A Novel Approach for Identification of Cancer Cells Using a Photonic Crystal Fiber-Based Sensor in the Terahertz Regime", Plasmonics 18(5), 1 (2023). CrossRef A. Yasli, "Cancer Detection with Surface Plasmon Resonance-Based Photonic Crystal Fiber Biosensor", Plasmonics 16(12), 1 (2021). CrossRef N. Ayyanar, G.T. Raja, M. Sharma, D.S. Kumar, "Photonic Crystal Fiber-Based Refractive Index Sensor for Early Detection of Cancer", IEEE Sensors Journal, 18(17), 7093 (2018). CrossRef S. Sharma, S. Das, C.S. Shieh et al. "Design and Numerical Analysis of a Gold-Coated Photonic Crystal Fiber Sensor for Metabolic Disorder Detection with Deep Learning Assistance", Plasmonics (2025). CrossRef R. Kasztelanic et al., "Influence of the core shape on the quality of fiber sensors based on D-shape fiber", Photon. Lett. Poland 16(3), 43 (2024). CrossRef S. Sharma, L. Tharani, "Photonics for AI and AI for photonics integration : Materials and characteristics", J. Inform. Optim. Sciences 45(3), 805 (2024). CrossRef